Developmental toxicity of cocaine exposure in mid-pregnancy mice. - SONG Jun; GUAN Xiao-Wei; REN Jia-Qian; HE Wei (Acta Pharmacologica Sinica; Vol 23, No 11 (November 2002): Acta Pharmacologica Sinica, 2016)
AIM: To investigate the toxic effects of mid-pregnancy cocaine exposure on embryo-fetus. METHODS: A transplacental murine model of cocaine exposure on embryo-fetus mice was established, in which pregnant dams of comparable weight were assigned into three groups: cocaine with food ad lib (COC), saline and pair-fed with COC (SPF), and saline with food ad lib (SAL). From embryonic d 8 (E8) to E17, physiological variables of dams and offspring were recorded and concentrations of dopamine and serotonin in fetal striatum were examined. RESULTS: Compared with SAL dams, COC and SPF dams showed lower weight gain. But only COC fetuses demonstrated low brain weight and low striatum weight on E17, as well as small biparietal diameter (BPD) on postnatal d1 (P1). Surprisingly, low brain/body weight ratio was seen in COC offspring, which might reflect disproportionate growth delay in these fetuses. Neurotransmitter and histological analysis revealed high level of dopamine and serotonin in COC fetal striatum, as well as morphological alterations of liver. CONCLUSION: Mid-pregnancy cocaine exposure induces fetal growth delay in utero, especially disproportionate brain developmental retardation. Maternal undernutrition does not play a key role in fetal developmental retardation when exposed to cocaine in utero.